PENGARUH PENYULUHAN TERHADAP PENGETAHUAN GIZI SEIMBANG PADA MASA PANDEMI COVID 19 - ravi masitah (IKesT Muhammadiyah Palembang, 2023)
Introduction: The COVID-19 pandemic is an infectious disease that attacks the respiratory system that has an impact on a person's health and quality of life. Consumption of nutritionally balanced foods is one of the efforts that can be made to improve the immune system during a pandemic and maintain optimal health status. Therefore, knowledge of balanced nutrition is needed to support the implementation of balanced nutrition attitudes and behaviors during the pandemic. Purpose: Activities are carried out to determine the influence of counseling on balanced nutrition knowledge during the Covid-19 pandemic. Method: The method used is counseling followed by discussion and question and answer activities. Devotion uses Quasi Experimental design with one group pre-test and post-test design. The service activity involved 20 participants of mothers in Seberang Ulu II Subdistrict, Kelurahan 13 Ulu RT 19. Results: Based on the results of statistical analysis, it is known that there is an influence of counseling on balanced nutrition knowledge during the Covid-19 pandemic (p-value < 0.005). Conclusion: Nutrition counseling can be an intervention given to increase knowledge of balanced nutrition so that it is hoped that there will be changes in attitudes and behaviors that affect nutritional status and health during the Covid-19 pandemic.